An Intersection under Stress: Diagnosing Layout and Control Issues - A Case Study at Srijana Chowk, Pokhara - Dhungana, Saroj (International Journal on Engineering Technology, 2025)
Srijana Chowk, a major intersection in Pokhara, Nepal, connects four critical roadways and experiences chronic congestion due to geometric and signal control deficiencies. This research aims to uncover the underlying issues affecting the intersection's performance, focusing on vehicular delay, structural obstruction, and driver frustration. Field data were collected through manual measurements of signal timings, queue lengths during red phases, and a series of perception-based surveys targeting drivers, pedestrians, nearby residents, and traffic police. Observations revealed that the central support pillar of an overhead skywalk exacerbated the obstruction of traffic flow, especially during peak hours. The lack of designated turning lanes, particularly for left turns on the north and south approaches, causes vehicles to block each other, resulting in increased noise pollution and unsafe conditions for pedestrians. Additionally, a curbside bus-stop on the southern approach was found to severely disrupt lane usage and create prolong queuing conflicts. Based on these findings, the study recommends minor geometric widening of approach lanes, introduction of no-horn signage, reconsidering the pillar placement, recessed bus bay further downstream and revision of traffic signal phasing to match observed queue dynamics better. Despite data collection limitations, this research highlights the pressing need for targeted interventions at Srijana Chowk and offers practical, low-cost recommendations for improving intersection control and safety in rapidly urbanizing areas.